PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL AYUNG RESORT UBUD BALI (Studi Pada Ayung Resort Ubud, Bali) - Ni Kadek Trisna Dewi; Made Yudi Darmita (Universitas Triatma Mulya, 2020)
Hotel Ayung Resort Ubud Bali is one of the companies engaged in accommodation that provides lodging services, provides food and beverages and other services where all services are allocated to everyone stay in hotels or use other facilities. Based on employee attendance data at Ayung Resort Ubud Bali Hotel, can be seen how the level of employee work discipline towards company attendance shows an average absentee level of 3.72% above 3% which is stated less. This can be seen in a fairly high level of complaint, with an average of 49.19% compared to the average good comment of 50.81%. The sample taken in this study amounted to 80 people 50% of the total employees with the sampling technique is proportional stratified random sampling. The data analysis tool used is descriptive analysis, data quality test, classic assumption test and multiple linear regression test with the Application Package for Social Science (SPSS) version 22.0. The results of research on motivation and work discipline have effect of 68.3% on employee performance at Ayung Resort Ubud Bali. While the remaining 31.7% is influenced by other variables not discussed in this study as: training, work environment, communication, leadership style and others. Hypothesis test results of effect of motivation (X1) on employee performance (Y) show a significance level of 0,000 smaller than α = 0.05. This means that motivation employee performance. Motivational regression coefficient (X1) of 3,667 shows the positive influence of motivation on employee performance. These results accept the hypothesis H1 which states that motivation has a positive effect on employee performance and the resultsof the work discipline hypothesis test (X2) on employee performance (Y) show a significance level of 0,000 smaller than α = 0.05. This means work disciplinevariables effect employee performance. Regression coefficient value of work discipline variable (X2) of 10,823 shows the positive influence of work discipline on employee performance. This result accepts hypothesis H2 which states that work discipline has a positive effect on employee performance.